2008
DOI: 10.1177/000348940811700607
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural Hearing Impairment in Children with Chiari I Malformation

Abstract: Chiari I malformation may be associated with SNHI. Central nervous system imaging for the evaluation of children with SNHI may be indicated, particularly in individuals with negative results on temporal bone computed tomography and genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, two patients had fluctuating loss. Patient 1 had a Chiari I malformation, which has been associated with sensorineural hearing loss 12, 13. Although this may have contributed to the severity of her deficit as well as its fluctuating nature, it would not explain the conductive component of her hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, two patients had fluctuating loss. Patient 1 had a Chiari I malformation, which has been associated with sensorineural hearing loss 12, 13. Although this may have contributed to the severity of her deficit as well as its fluctuating nature, it would not explain the conductive component of her hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…The association of CM 1 with hearing loss has been showed in pediatric age group previously. 5 Aside from that study, there are very limited reported studies and case reports on this topic. 3,4,6Y8 Our study seems to be the first to evaluate the association between cerebellar tonsil descent along with CM 1 with SHL.…”
Section: Discussionmentioning
confidence: 90%
“…Simons et al 5 had performed a retrospective evaluation of 113 children with SHL and found 6 patients having Chiari malformation (5.3%) that was much more common than the general population, in which the incidence of CM 1 has been cited to be between 0.56% and 0.77%. 4,5 Besides, there are only a few case reports on the association between hearing loss and CM 1 published in the literature. Although a few aforementioned reports are present on this subject, to the best of our knowledge, ectopia of cerebellar tonsils along with CM 1 in SHL has not been studied previously.…”
mentioning
confidence: 99%
“…Chiari I malformations and intracranial tumors are rare etiologies of UHL, but are an impetus for using MRI to image the temporal bones. 22,26 In children, acquired UHL from intrauterine infections (including cytomegalovirus [CMV]), meningitis, head trauma, otologic surgery, and ototoxic medications are well known, but is much less likely to result from removal of acoustic tumors than in adults. 27 Sudden SNHL is often unilateral and includes enlarged vestibular aqueduct, endolymphatic hydrops, trauma, perilymph fistula, 28 autoimmune, and idiopathic etiologies.…”
Section: Causes Of Uhl In Childrenmentioning
confidence: 99%